A review of posterior tibial nerve stimulation for faecal incontinence. (25th April 2013) - Thomas, G. P.; Dudding, T. C.; Rahbour, G.; Nicholls, R. J.; Vaizey, C. J.
Abstract Aim This review aimed to assess the published results of posterior tibial nerve stimulation (PTNS) for faecal incontinence. Method A search was performed of PubMed, MEDLINE and Embase to identify studies describing the clinical outcome of PTNS for faecal incontinence. Results Thirteen studies were identified. These described the outcome of PTNS for faecal incontinence in 273 patients. Four described transcutaneous PTNS, eight percutaneous PTNS and one compared both methods of PTNS with a sham transcutaneous group. One investigated patients with faecal incontinence and spinal cord injury and another with inflammatory bowel disease. There was marked heterogeneity of the treatment regimens and of the end points used. All reported that PTNS improved faecal incontinence. A > 50% improvement was reported in episodes of faecal incontinence in 63–82% of patients. An improvement was seen in urgency (1–5 min). Improvement was also described in the Cleveland Clinic faecal incontinence score in eight studies. Patients with urge and mixed incontinence appear to benefit more than those with passive incontinence. Treatment regimens ranged in duration from 1–3 months. A residual therapeutic effect is seen after completion of treatment. Follow‐up ranged from 1–30 months. Conclusion PTNS is effective for faecal incontinence. However, many of the published studies are of poor quality. Comparison between studies is difficult owing to differences in the outcome measures used, technique of PTNS and the timing and duration of treatment.